Urolithin A (UA) attenuates ferroptosis in LPS-induced acute lung injury in mice by upregulating Keap1-Nrf2/HO-1 signaling pathway - Lou, Lejing; Wang, Min; He, Jingjing; Yang, Song; Meng, Fanxi; Wang, Shijia; Jin, Xiao; Cai, Jihao; Cai, Chang (Frontiers in Pharmacology, 2023)
Acute lung injury (ALI) refers to a life-threatening disease with high incidence and mortality rates. The novel programmed cell death type known as ferroptosis exhibits features of lipid peroxidation and iron deposition. It has been proposed that ferroptosis can be a useful therapeutic target for many diseases, including ALI. One of the intestinal metabolites produced by ellagic acid-containing foods such as pomegranates, walnuts, or berries is Urolithin A (UA). Although it has been highly effective in treating different disorders, its impact on treatment for ALI remains largely unclear. The current study created two injured models through LPS treatment, one BEAS-2B cell injury model and one ALI mouse model. We found UA restored LPS-induced inflammation and oxidative stress. By stimulating the Nrf2 pathway, UA inhibited ferroptosis in a mechanism that prevented LPS-caused injuries to mice and BEAS-2B cells. Additionally, UA’s protection from LPS-mediated ALI and BEAS-2B cell injury was eliminated by an Nrf2 inhibitor (ML385). Together, these findings showed that UA prevented ferroptosis caused by LPS-mediated ALI through activating Nrf2, which may represent a novel potential therapeutic target for ALI.